-(2y+4)+3(2y+4)-2y=

Simple and best practice solution for -(2y+4)+3(2y+4)-2y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2y+4)+3(2y+4)-2y= equation:


Simplifying
-1(2y + 4) + 3(2y + 4) + -2y = 0

Reorder the terms:
-1(4 + 2y) + 3(2y + 4) + -2y = 0
(4 * -1 + 2y * -1) + 3(2y + 4) + -2y = 0
(-4 + -2y) + 3(2y + 4) + -2y = 0

Reorder the terms:
-4 + -2y + 3(4 + 2y) + -2y = 0
-4 + -2y + (4 * 3 + 2y * 3) + -2y = 0
-4 + -2y + (12 + 6y) + -2y = 0

Reorder the terms:
-4 + 12 + -2y + 6y + -2y = 0

Combine like terms: -4 + 12 = 8
8 + -2y + 6y + -2y = 0

Combine like terms: -2y + 6y = 4y
8 + 4y + -2y = 0

Combine like terms: 4y + -2y = 2y
8 + 2y = 0

Solving
8 + 2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 2y = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 2y = 0 + -8
2y = 0 + -8

Combine like terms: 0 + -8 = -8
2y = -8

Divide each side by '2'.
y = -4

Simplifying
y = -4

See similar equations:

| ax-b=d-cx | | 4x^4-5x^3-2x^2=0 | | -10+6=-7x+-9 | | 3-4x-5=-2 | | 0.25(12+4x)-0.5(8+2x)=0 | | 5x+6y-17=0 | | -8x+3(1-8x)=-4x+31 | | 0.25(12+4x)-0.5(8+2x)= | | x^3*x^6*x^9= | | 5=-3b-4-3 | | 3x^3+16x^2+15x-18=0 | | 11=n/6-5 | | 2x-8=-3x+2 | | 1-3p-1=-18 | | 11-7x=107-28x | | 21=43-2r | | 2(x+3)=x-13 | | 52=5d+7 | | w-22= | | a/12-3=2 | | 2(x+3)+4x=6+6x | | 69-2x=16x+19 | | 1.3(x-13)=14 | | 9x+20y=85 | | 6x^3+7x^2-3x= | | -10x=2x^2 | | .5n+5n=7n-18 | | -5x+8x-33=21 | | (x-9)-(-5+3)=1 | | 0.6(x-13)=14 | | 6x^2+7x^2-3x= | | 10+(-11)+(-12)= |

Equations solver categories